(untitled) (Journal of Engineering, 2008)
Housing planning is one of the most important subjects in the housing sector studies. It is wide and has many branches . . Housing planning according to the cost and social benefit is the solution to prevent the escalating rise in Housing shortage . This fact is combined with which is estimated at more than three million housing unit . And big a reduction in housing construction rate , which lead to increase the housing problem in the country. This matter needs a clear policy from the authorities to accelerate the planning process and to adopt that strategy to solve the housing problem in Iraq. This strategy should adopt the principal of constructing low – cost housing complexes through the construction of multi-stories unit (3-4 stories) , the economic results will be decrease in case of increase the stories to more than (4) stories because of the buildings required to the lift and other services, as aresult the cost of the execution and maintenance will be increase, especially when the technical cadres and the technology of the building and the administration were unimproved , in addition to other psychological elements resulting from the highly buildings , there is no domain to talk about it . and of the efficient characteristics which these units have suitable residential densities , active and economic land use and reducing the housing cost to face the big shortage and increased housing demand. The research has conducted a field study of three housing complexes (3-5) stories for the purpose of evaluating this type of housing and the extent if serves the social benefit and complain to design and planning criteria proposed in the General housing plan for Iraq. The research employ (cost & Benefit Analysis) to choose the best alternative from three housing complexes (hay Alsalam , Ziyona , Alsaidia) which serves low cost and best benefit.The research concludes to the importance of depending housing complexes (3-4) stories , and using light weight concrete is emphasized which one of the alternative for traditional building materials as bricks which has many specifications , saving in cost and labor , and reduction in time of construction , and solve of environment cases ,and choose the best alternative from three housing complexes (hay Alsalam , Ziyona , Alsaidia) which serves low cost and best benefit .